2014
DOI: 10.1002/ange.201406112
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Selectivity in the Chlorine Evolution Reaction over RuO2‐Based Catalysts

Kai S. Exner,
Josef Anton,
Timo Jacob
et al.

Abstract: In the industrially important Chlor-Alkali process, the chlorine evolution reaction (CER) over a ruthenium dioxide (RuO 2 ) catalyst competes with the oxygen evolution reaction (OER). This selectivity issue is elucidated on the microscopic level with the single-crystalline model electrode RuO 2 (110) by employing density functional theory (DFT) calculations in combination with the concept of volcano plots. We demonstrate that one monolayer of TiO 2 (110) supported on RuO 2 (110) enhances the selectivity toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…Table 1 Thermodynamic analysis of the competing oxidation processes for CA or chitosan oxidation. The change in energy (ΔHox) is determined by evaluating bonding energies from thermodynamic data tables [38], while the change in entropy (ΔSox) is obtained by taking only the standard entropies of CO2 and H2O into account assuming that the entropy change between the organic molecules is negligible small [39,40]. The free energy (ΔGox) of the corresponding oxidation process is calculated according to Eq.…”
Section: Reaction Mechanism Of Gnp Formation In Presence Of Chitosan mentioning
confidence: 99%
“…Table 1 Thermodynamic analysis of the competing oxidation processes for CA or chitosan oxidation. The change in energy (ΔHox) is determined by evaluating bonding energies from thermodynamic data tables [38], while the change in entropy (ΔSox) is obtained by taking only the standard entropies of CO2 and H2O into account assuming that the entropy change between the organic molecules is negligible small [39,40]. The free energy (ΔGox) of the corresponding oxidation process is calculated according to Eq.…”
Section: Reaction Mechanism Of Gnp Formation In Presence Of Chitosan mentioning
confidence: 99%
“…RuO 2 is an active catalytic material in a variety of processes, including catalytic CO [1][2][3], NH 3 [4], alcohol [5], and Hg oxidation [6], as well as in electrochemical phenolic wastewater oxidation [7], or as an anode in water splitting cells [8]. In addition to its electrochemical applications [9,10], one of the most significant industrial uses of RuO 2 is in HCl oxidation (Deacon process), where it is the best performing catalyst to produce molecular chlorine at low temperature [11][12][13][14]. Therefore, the chemistries of oxygen and chlorine on the RuO 2 surfaces are intertwined, as evidenced by the linear scaling relationships (Cl and O energies scale one with the other) [15,16] and thus the material is prone to exhibit a complex selectivity behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the chemistries of oxygen and chlorine on the RuO 2 surfaces are intertwined, as evidenced by the linear scaling relationships (Cl and O energies scale one with the other) [15,16] and thus the material is prone to exhibit a complex selectivity behaviour. In fact, when seawater is employed in a RuO 2 -based electrochemical water splitting cell, the selectivity towards the O 2 evolution reaction is compromised as Cl 2 evolution emerges as a competitive path [10,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed metal oxides (MMOs) based on precious metals (Ru and Ir), such as a dimensionally stable anode (DSA), have been predominantly used as CER catalysts irrespective of the pH of the solution [5][6][7][8] . However, computational and experimental works revealed that MMO catalysts are also highly active for the OER, exhibiting a scaling relationship between the CER and OER 13,[17][18][19][20] . This relationship suggests that two reactions are catalysed on a similar active site of the MMOs or form a common surface intermediate species [20][21][22][23][24] .…”
mentioning
confidence: 99%